B7H6 Serves as a Negative Prognostic Marker and an Immune Modulator in Human Pancreatic Cancer - Zhu, Zheng; Teng, Kun-Yu; Zhou, Jian; Xu, Yunyun; Zhang, Lifeng; Zhao, Hua; Zhang, Xueguang; Tian, Lei; Li, Zhiyao; Lu, Ting; Ma, Shoubao; Li, Zhenlong; et al. (Frontiers in Oncology, 2022)
Pancreatic cancer (PC), the third leading cause of cancer-related death in the U.S., is frequently found too late to be cured by traditional chemotherapy. Expression of B7 homolog 6 (B7H6), a member of the B7 family of immunoreceptors, has been found in PC and several other cancers. B7H6 is a ligand for cytotoxicity triggering receptor 3 (NKp30), which is expressed on NK cells. Here, we demonstrate that B7H6 can be detected in PC tissues but not normal organs. Its expression in patients associated significantly with tumor differentiation grade and lymphatic metastasis. The soluble form of B7H6 was detected in the PC patients’ sera and its concentration associated with tumor differentiation grade and tumor, node, metastasis (TNM) stages. Also, higher levels of B7H6 in PC patients’ malignant tissues or serum correlated with shorter overall survival. In vitro, downregulation of B7H6 by CRISPR/Cas9 or siRNA technology had no significant impact on the viability or mobility of PC cells. Instead, knocking out B7H6 sensitized PC cells to NK-mediated cytotoxicity and cytokine production. These results indicate that B7H6 not only serves as a negative prognostic marker but also acts as an immune modulator in PC.